La eficacia personal del convenio colectivo de trabajo: Idas y venidas sobre la extensión unilateral del convenio colectivo a los trabajadores no sindicalizados - Boza Pró, Guillermo; Briones Zegarra, Joaquín (Pontificia Universidad Católica del Perú, 2024)
The unilateral extension of the collective agreement has been widely discussed by Peruvian doctrine and jurisprudence for more than a decade. Aside from this, it maintains its validity to the extent that there is still a contrast in positions between two decision-making bodies of the Peruvian labor legal system. This article addresses the topic with the purpose of establishing a position on the debate, developing its analysis in three sections. Firstly, basic issues relating to the collective agreement as a bargaining product, its legal effectiveness and its personal effectiveness related to the criterion of greater representativeness are reviewed. Secondly, the jurisprudential evolution that the topic has had in the decisions of the Supreme Court, such as those of the Labour Inspection Court of the National Superintendence of Labour Inspection, is detailed; in such a way that the authors mark their position on the arguments outlined in each case. Next, a rarely touched upon aspect of the theme is developed; that is, the possibility for non-unionized workers to retain the benefits unilaterally extended by the employer. The article ends with some brief conclusions on what has been reflected.

La extensión unilateral del convenio colectivo es un tema que ha sido ampliamente tratado por la doctrina y jurisprudencia peruana desde hace más de una década. Al margen de ello, mantiene su vigencia en la medida que aún existe una contraposición de posturas entre dos órganos resolutivos del ordenamiento jurídico laboral peruano. El presente artículo aborda el tema con el objetivo de sentar postura sobre el debate, desarrollando su análisis en tres secciones. En primer lugar, se repasan cuestiones básicas referidas al convenio colectivo como producto negocial, su eficacia jurídica y su eficacia personal relacionada con el criterio de mayor representatividad. En segundo lugar, se detalla la evolución jurisprudencial que el tema ha tenido en las decisiones de la Corte Suprema, como en las del Tribunal de Fiscalización Laboral de la SUNAFIL, de forma tal que los autores marcan su posición sobre los argumentos esbozados en cada caso. Seguidamente, se aborda una arista del tema no tan desarrollada, esto es, la posibilidad de que los trabajadores no sindicalizados conserven los beneficios extendidos unilateralmente por el empleador. Finaliza el artículo con unas breves conclusiones sobre lo reflexionado.
The personal effectiveness of the collective agreement: Comings and goings on the unilateral extension of the collective agreement
Keywords: Unilateral extension of collective agreement; Freedom of association; Principle of equal treatment; Union representation; Supreme Court; Labour Inspection Court of the National Superintendence of Labour Inspection; Extensión unilateral del convenio colectivo; Libertad sindical; Principio de igualdad; Representación sindical; Corte Suprema; Tribunal de Fiscalización Laboral de la SUNAFIL; https://purl.org/pe-repo/ocde/ford#5.05.00